The journey home [videorecording (DVD)] - Goyo, Dakota, 1999-; Visnjic, Goran, 1972-; Moynahan, Bridget, 1971-; Spottiswoode, Roger; Quilici, Brando; Gavigan, Bart; McDonald, Winston (Image Entertainment, 2015)
When Luke discovers that a young polar bear cub has been separated from his mother, he sets out to find a way to reunite the two. Setting out across a frozen landscape, it is up to Luke to protect himself and the cub from the dangers of the wild and the elements to help the cub find his way home.